Evaluation of prerequisite programs implementation at schools foodservice - Liz Martins, Margarida (2014)
Introduction: Strengthening food safety measures in schools would improve protection of students andschool staff from outbreaks of foodborne illness. The main objective of this study was to evaluate thenon-conformities in prerequisite programs implementation at school foodservice.Methods: This descriptive study was conducted between October and December 2011 involving 88school foodservice units at a Portuguese Municipality. Each school foodservice was audited using ahygiene-sanitary checklist including 146 statements by the same nutritionist. Prerequisite programprocedures were evaluated after categorization as standard operating procedures, sanitation and hygieneprocedures and procedures for receiving and storage of foods. Food safety procedures and practices werecompared between cooking and distribution food units and according to the number of meals produceddaily.Results: Non conformities were detected concerning several safety practices such as incorrect thawing,temperature control of freezing equipment and cooked food, segregation between stored food and detergentsand disinfectants, procedures used for handling waste, cleaning and sanitizing.Only 40% of foodservice units evaluated recorded temperature of cooked meals. All foodservice unitsaudited revealed non conformities on cleaning and disinfection practices of equipment and facilities.Adequate labeling of stored items was properly done at 85% of units. Handling waste was undertakenincorrectly by all food handlers in this survey.Reasons identified for inappropriate personal hygiene practices were mainly lack of resources andconditions for correct hand washing procedure.No significant relationship was found between food safety procedures and practices and number ofmeals produced or served. Distribution food units failed safety checks in aspects such as food-handlingpractices and temperature control of cooked meals, more frequently than cooking units.Conclusion: Results indicate an urgent need for food safety training of personnel and point out to theneed of continuous supervision by managers. It is also important to define standard operating proceduresthat include food safety components and improve employee motivation and responsibility.